PRINCIPLES OF GOOD GOVERNANCE IN PUBLIC MANAGEMENT OF EDUCATIONAL DEVELOPMENT AT THE LOCAL LEVEL - Yushkevych, Yuliia (Current Problems of Sustainable Development, 2026)
The article comprehensively substantiates the theoretical and applied foundations and identifies the specifics of implementing the basic principles of the Good Governance concept in the process of public management of educational development at the local level in Ukraine. A comparative analysis of primary European standards, in particular the «White Paper on European Governance» and the Council of Europe Strategy, with the domestic regulatory and legal framework is carried out. The author explores the temporal dynamics of the implementation of these principles through the lens of evaluation criteria of the international SIGMA standard. Based on the study of the advanced municipal experience of Estonia, Finland, and Poland, the high efficiency of deep decentralization, digitalization, and building management systems based on trust and participation is proved. The research reveals a complex of chronic destructions in modern Ukrainian educational management practice, including mock participation, a crisis of accountability, and risks of recentralization under security challenges. The transformational impact of the new Strategy for Reforming the State Financial Management System for 2026-2030 on local education is thoroughly substantiated. It is proven that the introduction of such tools as cascading objectives, three-year medium-term budgeting, integrated e-audit systems, and funding based on key performance indicators (KPIs) allows overcoming existing destructions, eliminating managerial isolation,  and ensuring the sustainability and autonomy of the educational space in communities. The practical value of the study lies in the systematization of transition phases towards automated oversight, which minimizes human factors and administrative corruption, creating an institutional framework for sustainable post-war educational recovery.
Keywords: educational management; Governance; decentralization; municipal management; public administration; territorial community